Unbalanced segregation of a paternal t(9;11)(p24.3;p15.4) translocation causing familial Beckwith-Wiedemann syndrome: a case report - Caroline Lekszas; Indrajit Nanda; Barbara Vona; Julia Böck; Farah Ashrafzadeh; Nahid Donyadideh; Farnoosh Ebrahimzadeh; Najmeh Ahangari; Reza Maroofian; Ehsan Ghayoor Karimiani; Thomas Haaf (BMC, 2019)
Abstract Background The vast majority of cases with Beckwith-Wiedemann syndrome (BWS) are caused by a molecular defect in the imprinted chromosome region 11p15.5. The underlying mechanisms include epimutations, uniparental disomy, copy number variations, and structural rearrangements. In addition, maternal loss-of-function mutations in CDKN1C are found. Despite growing knowledge on BWS pathogenesis, up to 20% of patients with BWS phenotype remain without molecular diagnosis. Case presentation Herein, we report an Iranian family with two females affected with BWS in different generations. Bisulfite pyrosequencing revealed hypermethylation of the H19/IGF2: intergenic differentially methylated region (IG DMR), also known as imprinting center 1 (IC1) and hypomethylation of the KCNQ1OT1: transcriptional start site (TSS) DMR (IC2). Array CGH demonstrated an 8 Mb duplication on chromosome 11p15.5p15.4 (205,827-8,150,933) and a 1 Mb deletion on chromosome 9p24.3 (209,020-1,288,114). Chromosome painting revealed that this duplication-deficiency in both patients is due to unbalanced segregation of a paternal reciprocal t(9;11)(p24.3;p15.4) translocation. Conclusions This is the first report of a paternally inherited unbalanced translocation between the chromosome 9 and 11 short arms underlying familial BWS. Copy number variations involving the 11p15.5 region are detected by the consensus diagnostic algorithm. However, in complex cases which do not only affect the BWS region itself, characterization of submicroscopic chromosome rearrangements can assist to estimate the recurrence risk and possible phenotypic outcomes.